Bio-Fabrication and Experimental Validation of an Mg - 25Ca - 5Zn Alloy Proposed for a Porous Metallic Scaffold - Campos Becerra, Luis Humberto; Torres Castro, Alejandro (Molecular Diversity Preservation International, 2021)
This paper proposes the bio-fabrication of a porous scaffold from a selection procedure of elements taking into account biological behavior, using magnesium (Mg) alloyed with calcium (Ca) and zinc (Zn). The proposed scaffold could work as a treatment for specific pathologies in trauma and oncology, on the one hand, in addition to possible applications in osteosynthesis, through contrib-uting to osseointegration and infection control through the release of drugs. Finally, another pos-sible attribute of this alloy could be its use as a complementary treatment for osteosarcoma; this is due to the basification produced by oxidative degradation (attack on cancer cells). The evaluation of cell viability of an alloy of Mg - 25 wt% Ca - 5 wt% Zn will strengthen current perspectives on the use of Mg in the clinical evaluation of various treatments in trauma and oncology. Considera-tions on the preparation of an alloy of Mg - 25 wt% Ca - 5 wt% Zn and its morphological charac-terization will help researchers understand its applicability for the development of new surgical techniques and lead to a deeper investigation of alternative treatments. However, it is very im-portant to bear in mind the mechanical effect of elements such as Ca and Zn on the degradation of the alloy matrix; the best alternative to predict the biological-mechanical potential starts with the selection of the essential-nutritional elements and their mechanical evaluation by mi-cro-indentation due to the fragility of the matrix. Therefore, the morphological evaluation of the specimens of Mg - 25 wt% Ca - 5 wt% Zn will show the crystallinity of the alloy; these results to-gether contribute to the design of biomedical alloys for use in treatments for various medical spe-cialties. The results indicated that cell viability is not affected, and there are no morphological changes in the cells.